CBMT-22. REVERSING THE WARBURG EFFECT BY TARGETING NICOTINAMIDE PHOSPHORIBOSYLTRANSFERASE (NAMPT), THE RATE-LIMITING ENZYME OF NAD+ SALVAGE PATHWAY INCREASES, CHEMOSENSITIVITY TO TEMOZOLOMIDE IN GLIOMA CELLS. (11th November 2019) - Sharma, Pratibha; Senapedis, William; Sampath, Deepa; Puduvalli, Vinay
Abstract: BACKGROUND: Glioma cells metabolize glucose primarily through incomplete, non-oxidative glycolysis even in the presence of oxygen (the Warburg effect) which provides a constant supply of substrate for proliferation and generates an acidic environment that favors invasion and immunosuppression. NAMPT, the rate-limiting enzyme of the NAD+ salvage pathway, regulates key metabolic processes preferentially used in glioma energy metabolism. Inhibition of NAMPT could have global impact on glioma cell metabolism and could be a promising strategy for glioma therapy. This study examined the effect of NAMPT inhibition using KPT-9274 and FK866 (NAMPTi) on glycolysis and glioma cell metabolism. METHODS: Metabolic changes related to NAMPT inhibition were examined in glioma cell lines and patient derived glioma stem-like cells (GSC). Mass spectrometry was used for metabolic profiles and the generated data was annotated by comparison against an extensive metabolite library to identify relevant metabolites. The Agilent Seahorse assay was utilized to determine treatment-related changes in glycolysis. RESULTS: NAMPT inhibition caused NAD, NADH, NADP, NADPH, and ATP depletion in glioma cells. Global metabolomics results showed an accumulation of GMP, IMP, AMP and myo-inositol indicating reprogramming of glioma cell metabolism for de novo purine biosynthesis. Additionally, an accumulation of glucose- and fructose-1, 6 bisphosphate in NAMPTi treated cells indicated dysfunctional glycolysis. This was confirmed by the Agilent glycolysis stress test by which NAMPTi-treated glioma cells showed a reduction in glycolysis, glycolytic capacity and reserves. NAMPTi treated cells showed downregulation of LDHA due to NAD depletion. Further, downregulation of LDHA enhanced the chemosensitivity of glioma cells to temozolomide. CONCLUSIONS: NAMPTi cause profound disruption of glycolysis, reduced glycolytic capacity and glycolytic reserve in gliomas and GSCs irrespective of O[6]-methylguanine-DNA methyltransferase promoter methylation or IDH1 status. Targeting NAMPT to disrupt the Warburg effect is a novel strategy for developing effective therapies against glioma to overcome heterogeneity.